2015
DOI: 10.1002/2015ja021025
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of mesoscale thermospheric wind structure using a network of interferometers

Abstract: We introduce a technique for estimating the regional thermospheric wind field from measurements made by a network of interferometers. Unlike previous work, this technique does not make assumptions about the functional form of the wind field and instead uses inverse theory to find the smoothest wind field that agrees with the measurements. This technique is general and applies to any network making radial velocity measurements. We show reconstructions of the thermospheric wind field over the eastern United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…Both of these conditions can occur as a result of the MTM. At El Leoncito, the observations presented here show that the BW travels South‐West and previous studies have shown that the MTM is known to create or enhance a poleward wind (Harding et al, ; Meriwether et al, ). It is this poleward wind that moves the plasma and creates the BW.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Both of these conditions can occur as a result of the MTM. At El Leoncito, the observations presented here show that the BW travels South‐West and previous studies have shown that the MTM is known to create or enhance a poleward wind (Harding et al, ; Meriwether et al, ). It is this poleward wind that moves the plasma and creates the BW.…”
Section: Discussionsupporting
confidence: 63%
“…Regarding the zonal winds, past observations have shown that the MTM can cause a reversal or abatement in the typically eastward zonal wind (Colerico et al, ; Harding et al, ; Meriwether et al, ). This reversal due to the MTM can cause a convergence of the zonal wind in the same way as the common reversal near sunrise.…”
Section: Discussionmentioning
confidence: 99%
“…It is described, for example, by Bristow et al () and Nicolls et al () as a means of inverting radar measurements of Doppler shift to derive ion flow vectors. Of more direct relevance here is the work of Harding et al (), who used a regularized inverse approach to estimate the thermospheric neutral wind field from a midlatitude array of narrow‐field Fabry‐Perot instruments.…”
Section: Multistatic Fabry‐perot Wind Fittingmentioning
confidence: 99%
“…We propose to further investigate ways to reduce the inverse problem's condition number, and its sensitivity to outliers. We note in this context that to deal with fitting radial velocities to multisite FPI observations, Harding et al (2015) successfully regularized the inversion problem in such a way as to produce "smooth" variations in the solved components. It is not clear how well the approach will lend itself to non-ideal observing geometries in the covariance estimation situation, but it nonetheless appears promising, in particular for application to meteor radar estimates of wind covariance.…”
Section: Simulationsmentioning
confidence: 99%